Towards precision controlled 2D functional group patterning of graphene via laser writing - Nagel, Tamara; Wolff, Stefan; Feng, Sijia; Weber, Heiko B.; Maultzsch, Janina; Hauke, Frank; Hirsch, Andreas (Carbon, 2025)
We herein present a significant advance in the understanding of the reaction mechanisms and the influence of the laser “writing” parameters in the laser-triggered activation of dibenzoyl peroxides (DBPO) and the subsequent high-precision covalent patterning of functional groups on monolayer graphene. Our straightforward and versatile procedure allows a complete deconvolution of the laser-induced functional group grafting in the “writing” step from a competing functionalization in the corresponding Raman characterization by a full removal of the DBPO film after covalent group attachment. This allows an in-depth analysis and understanding of the underlying laser “writing” and “reading” parameters - laser power and irradiation time - and thus a precise control of the degree of functionalization. Furthermore, by optimizing these parameters, the lateral dimension limits of the individual graphene patterned structures can be scaled down to 1.5 μm, with the potential to further improve the pattern size to the nanoscale in combination with a lithographically etched mask approach.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Covalent functionalization; Graphene chemistry; Laser writing; Photochemistry; Precision structuring; Spatial control